1996
DOI: 10.1016/0040-6090(95)08073-2
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of the porous silicon photoluminescence by a multiphoton vibronic process

Abstract: We study the emission of photons from porous Si after high-level vibrational excitation in the Si-O absorption band using a pulsed CO2 laser. Narrow resonances in the efficiency of light generation are discovered at 1030 cm-~ and 1084 cm-i. For excitation at 1030 cm-m the familiar photoluminescence band of porous Si appears. Time-resolved pump-to-probe experiments show the same decay times for the photo and the IR-induced luminescence. We suggest a microscopic process responsible for the light emission.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Moreover, since no correlation between the quenching rate and the particle surface chemistry is observed, it is expected that the silicon structure is involved in leading to dark (nonemitting) clusters. These observations are in agreement with those by Diener and co-workers indicating that IR excitation of porous silicon results in a drop in the PL intensity but only with a slight change in the PL lifetime. The authors suggested that IR excitation creates additional dangling bonds or opens additional nonradiative channels leading to an increase of the fraction number of dark crystallites.…”
Section: Resultssupporting
confidence: 93%
“…Moreover, since no correlation between the quenching rate and the particle surface chemistry is observed, it is expected that the silicon structure is involved in leading to dark (nonemitting) clusters. These observations are in agreement with those by Diener and co-workers indicating that IR excitation of porous silicon results in a drop in the PL intensity but only with a slight change in the PL lifetime. The authors suggested that IR excitation creates additional dangling bonds or opens additional nonradiative channels leading to an increase of the fraction number of dark crystallites.…”
Section: Resultssupporting
confidence: 93%